A novel bioactive peptide-peptoid hybrid of alpha-calcitonin gene-related peptide protects against pressure-overload induced heart failure - Kumar, Ambrish; Deloach, Sarah; Williams, Lernix; DiPette, Donald J.; Potts, Jay D. (Frontiers in Pharmacology, 2025)
BackgroundAlpha-calcitonin gene-related peptide (α-CGRP) is a cardioprotective neuropeptide. However, due to low bioavailability, its use as a therapeutic agent is limited. The aim of the present study was to develop a stable and bioactive α-CGRP analog and to determine its cardioprotective effects in a mouse model of heart failure (HF).MethodsWe chemically synthesized a peptide-peptoid hybrid: human α-CGRP containing two monomers of N-methoxy-ethyl glycine peptoid at the N-terminus (NMEG-CGRP). The toxicity, bioactivity, and stability of NMEG-CGRP were determined by MTT-cell viability assay, mouse blood pressure measurement, and in-vitro digestion with Insulin-degrading enzyme (IDE) followed by LC-MS, respectively. Male C57BL6 mice were underwent transverse aortic constriction (TAC) and were divided into: Sham, Sham+NMEG-CGRP, TAC, and TAC+NMEG-CGRP. Two-day post-TAC, NMEG-CGRP (3.6 mg/kg/mouse) was administered subcutaneously on alternate days, for a total of 28 days. Cardiac function was measured weekly using echocardiography. At the endpoint, mice were euthanized, and hearts were collected for analysis.ResultsOur results demonstrated that NMEG-CGRP was non-toxic to rat H9C2 cells, more stable to IDE digestion, and bioactive. TAC-induced pressure-overload decreased ejection fraction and increased cardiac hypertrophy and dilation, fibrosis, apoptosis, oxidative stress, and macrophage infiltration in the left ventricles. NMEG-CGRP administration significantly attenuated these TAC-induced adverse cardiac effects in the HF mice.ConclusionTogether, our results demonstrated that NMEG-CGRP is a non-toxic, stable, and bioactive CGRP-analog, and protects against pressure-induced HF in mice. Thus, NMEG-CGRP is a promising novel CGRP-analog that may be used in the treatment of HF and potentially other cardiac diseases.